Hubungan penggunaan sosial media dan pengetahuan seks bebas pada siswa/siswi usia 17-18 Tahun - Hesti Wahyuningtias; Wahyu Wibisono (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2018)
Abstract: Many factors can affect teen sex knowledge (Students,) one of them is information media such as the social media. The purpose of this study was to determine the correlation of facebook and instagram usage with free sex knowledge of 17-18 years old students of senior high school PGRI TALUN Blitar. This design of the study was Corelational with Cross sectional design. The population in this study was all of students aged 17-18 years old of senior high school PGRI TALUN Blitar. The sample was 28 students. The sampling technique used Total Sampling. The Statistical test used Spearman Rank. The results showed that there were 85.7% of adolescents who used social media facebook and instagram 71.4% were in the category of good knowledge and 10.7% in the category of fair, while 4% of adolescents who did not use facebook and instagram 7.1% were in the category of good knowledge and 10.7% were in category of fair. The conclusion of was there wasa correlation of social media usage with studentss knowledge about free sex in SMA PGRI TALUN Blitar (p = 0,000). It is expected that school should be open minded on the digital technology, especially the social media so that students curiousity can be facilitated and monitored by school to prevent free sex. Keywords: Students, Free sex Knowledge, Social Media Abstrak: Banyak faktor yang dapat mempengaruhi pengetahuan seks remaja (Siswa) salah satunya adalah sumber informasi berupa media sosial. Tujuan peelitian ini adalah untuk mengetahui hubungan antara penggunaan media sosial dengan pengetahuan seks siswa SMA PGRI TALUN Blitar. Jenis penelitian ini merupakan korelasional dengan rancangan Cross sectional. Populasi dalam penelitian ini adalah remaja SMA PGRI TALUN Blitar dengan sampel 28 siswa. Tehnik pengambilan sampel ang digunakan adalah Total Sampling. Uji statistik menggunakan Spearman Rank. Hasil penelitian menunjukan bahwa terdapat 85,7 % remaja yang menggunakan media sosial facebook dan instagram memiliki pengetahuan baik sebesar 71,4 % dan cukup sebesar 10,7%. Sedangkan dari 4 % remaja yang tidak menggunakan facebook dan instagram meiliki pengetahuan baik dan cukup masing-masing sebesar 7,1% dan 10,7%. Kesimpulan dari penelitian ini adalah adanya hubungan penggunaan media sosial dengan pengetahuan remaja tentang seks bebas di SMA PGRI TALUN Blitar (p = 0,000) Kata kunci: Siswa, Pengetahuan seks , Media sosial